A Poliovirus Receptor (CD155)-Related Risk Signature Predicts the Prognosis of Bladder Cancer - Luo, Cong; Ye, Wenrui; Hu, Jiao; Othmane, Belaydi; Li, Huihuang; Chen, Jinbo; Zu, Xiongbing (Frontiers in Oncology, 2021)
Background Bladder cancer is an aggressive and heterogeneous disease associated with high morbidity and mortality. And poliovirus receptor (PVR or CD155) played crucial roles in tumor immune microenvironment and cancer development. However, their association remains obscure. Methods A total of 797 patients from TCGA and GEO databases were employed in our study, in which 285 cases were set as the training cohort and 512 were defined as the validation cohort. Our own Xiangya cohort with 57 samples was also used for the validation. Survival differences were evaluated by Kaplan-Meier analysis between groups. The immune infiltration was evaluated by ESTIMATE, TIMER, and CIBERSORT algorithms. The risk signature was constructed by LASSO Cox regression analysis. And a nomogram model was generated subsequent to the multivariate Cox proportional hazards analysis to predict 3- and 5-year survival of patients with bladder cancer. Results PVR was overexpressed across various cancers including bladder cancer and related to poorer overall survival in bladder urothelial carcinoma (BLCA). Samples with higher World Health Organization (WHO) grade or higher tumor stage tended to express higher level of PVR. And PVR-related genes were involved in several immune processes and oncological pathways. When the patients were divided into low- and high-risk groups based on their risk scores, we found that patients in the high-risk group had shorter overall survival time. Besides, samples with high risk were consistently correlated with tumor hallmarks and higher abundance of immune infiltration. Additionally, chemotherapy showed potent efficacy in high-risk group. Moreover, a nomogram including clinicopathologic features and the established risk signature could predict 3- and 5-year survival in patients with bladder cancer. Conclusion Our study revealed that PVR was overexpressed and related to poor prognosis in bladder cancer. A risk signature and nomogram model based on PVR-related genes could predict the prognosis and therapeutic efficacy and were also associated with the immune infiltration in bladder cancer.